WAKAF TUNAI DALAM PERSPEKTIF FIQIH DAN TEORI MAQASID SYARIAH - Beni, Beni Setyawan; Asmuni (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
Waqf is a form of worship which in the Qur'an is referred to as al-habs, a synonym for the word al-waqaf, namely someone's property that is given to the public so that it can be used as long as the item is still there. Along with the large need for funds for the benefit and locations spread outside the area for the wakif, the idea of ​​cash waqf emerged. With the convenience of cash waqf, people can easily spend their wealth as waqf in religious ways. This research aims to understand the law of cash waqf in the study of fiqh, by looking at several views of fiqh scholars regarding cash waqf and its benefits from a maqasid sharia perspective. This research uses a qualitative-descriptive approach with content analysis techniques in library research and problem analysis using maqasid asy-syariah theory. The results of the research show that the jurists have different opinions in determining the law on cash waqf. Some scholars believe that cash waqf is permissible. Others view the law as makruh. There are even scholars who prohibit it. The results of the study show that cash waqf is in accordance with the principles of maqasid sharia, namely to improve the economy and obtain benefits in this world and the hereafter.